1992
DOI: 10.1037/0735-7028.23.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-help books in psychotherapy.

Abstract: A survey concerning the recommendation of self-help books to clients was completed by 209 psychologists (66.5% male, 94.3% White, mean age = 45 years). Most of the respondents indicated that they did prescribe self-help books infrequently. The likelihood of prescribing books was significantly related to the psychologist's gender, with women recommending books more often than did men, and to employment setting, with private practitioners recommending books more often than did academicians. Psychologists had lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Mental health professionals often utilize bibliotherapy as an adjunct intervention. Research shows that most of the clinicians surveyed have used psychological self-help books in their practice and are satisfied with the results (Marx, Royalty, Gyorky, & Stern, 1992;Norcross et al, 2003;O'Connor & Kratochwill, 1999;Starker, 1988). Bibliotherapy shares and operates through the same healing processes as movies.…”
Section: Cinematherapy and Bibliotherapymentioning
confidence: 91%
“…Mental health professionals often utilize bibliotherapy as an adjunct intervention. Research shows that most of the clinicians surveyed have used psychological self-help books in their practice and are satisfied with the results (Marx, Royalty, Gyorky, & Stern, 1992;Norcross et al, 2003;O'Connor & Kratochwill, 1999;Starker, 1988). Bibliotherapy shares and operates through the same healing processes as movies.…”
Section: Cinematherapy and Bibliotherapymentioning
confidence: 91%
“…Several researchers have examined the use of self-help materials by mental health practitioners in the USA (e.g. Marx, Gyorky, Royalty, & Stern, 1992;Quackenbush, 1991;Starker, 1988) and UK (Keeley, Williams, & Shapiro, 2002). These surveys have shown that between 60.3 and 88.8 per cent of practitioners recommend or use such materials.…”
Section: Why Provide Self-help Treatments Within Clinical Services?mentioning
confidence: 98%
“…A project to collect information on self-help resources for women resulted in a publication by Marx, Gyorky, Royalty, and Stern (1992). The focus in the publications of the Committee on Women during the 1980s shifted from concerns about the sex bias of counselors and equity for women in the workplace to issues related to violence in the family, childhood sexual abuse and its aftermath, sexual harassment, and sexual relations of therapists with their clients.…”
Section: Counseling Needs Of Women Changementioning
confidence: 99%